Of boys and men : why the modern male is struggling, why it matters, and what to do about It - Reeves, Richard V. (Brookings Institution Press, 2022)
"Boys and men are struggling. Profound economic and social changes of recent decades have many losing ground in the classroom, the workplace, and in the family. While the lives of women have changed, the lives of many men have remained the same or even worsened. Our attitudes, our institutions, and our laws have failed to keep up. Conservative and progressive politicians, mired in their own ideological warfare, fail to provide thoughtful solutions. The father of three sons, a journalist, and a Brookings Institution scholar, Richard V. Reeves has spent twenty-five years worrying about boys both at home and work. His new book, Of Boys and Men, tackles the complex and urgent crisis of boyhood and manhood. Reeves looks at the structural challenges that face boys and men and offers fresh and innovative solutions that turn the page on the corrosive narrative that plagues this issue. Of Boys and Men argues that helping the other half of society does not mean giving up on the ideal of gender equality." --